From Political Won't to Political Will: Building Support for Participatory Governance - and Malena, Carmen (Kumarian Press, 2009)
* Geographically diverse examples of participatory governance in action* Practical case studies show how citizens can participate more fully in the political process Despite a recent wave of democratization around the world, traditional systems of representative democracy seem to be in crisis. Citizens in both the North and the South lack opportunities, rights and access to information and have expressed growing disillusionment with their governments. Ordinary citizens (especially women, poor people and other marginalized groups) are largely excluded from the political processes that directly affect their lives. There is now growing consensus that good governance is participatory governance (PG), but public officials are often reluctant to adopt such an approach. From Political Won’t to Political Will addresses the particular challenge of encouraging these officials to involve citizens in the political process. The book presents contributions by participants from CIVICUS’ 2008 conference on building political will for PG. Representing the perspectives of both civil society and government actors, they propose a number of strategies and lessons such as demonstrating the benefits of PG to governments, complementing formal democratic institutions, building trust, supporting PG champions and using strategic political timing. Their practical and highly original findings will interest anyone eager to see the empowerment of people around the world.